الأسلوب المعرفي (التروي/ الاندفاع) عند مدمني المخدرات - عزي صالح, نعيمة; صادقي, فاطمة (جامعة الوادي - University of Eloued, 2020)
إن هذه الدراسة تهدف إلى تسليط الضوء علي جانب من جوانب النظام المعرفي عند مدمن المخدرات و هو الأساليب المعرفية، و ذلك من خلال محاولة توضيح علاقة الأسلوب المعرفي )التروي/ الاندفاع ( بالإدمان على المخدرات، حيث يعتبر هذا الأخير من بين المواضيع التي استقطبت اهتمام الباحثين لما له من أثار صحية، نفسية، معرفية و اجتماعية سلبية على الفرد والمجتمع.Abstract: Drug-addiction is a hideous phenomenon leads to the spread of different devastating illnesses and the decadence of the ethics and the morals, effects the health psychological and cognition person life, especially in his cognitive style. Thisclinical study aims to presentthe relationbetween cognitive style (impulsivity /reflectivity)anddrug- addiction to four addicts in Tamanrasset city. We used the clinical interview and Kagan scale (Impulsivity/ Reflectivity), and the result was like our expectation (Addiction makes the individual impulsive, especially at poly-drug and early-drug.
مقال
Keywords: الأساليب المعرفية؛ الأسلوب المعرفي( التروي/ الاندفاع)؛ الإدمان على المخدرات؛ البداية المبكرة؛ تعداد المواد.; Addiction- drug; cognition styles; Impulsivity/ reflectivity- style; poly-drug; earlydru